Perspectives On Integrating Health Into The Low-Income Housing Tax Credit: A Qualitative Study - Shi, Marc (Health Aff (Millwood), 2020)
While there is increasing attention to the ways that safe and affordable housing may promote improved health, less work has focused on the role of the Low-Income Housing Tax Credit (LIHTC) program—the largest source of affordable housing in the United States. Through qualitative interviews, we examined the perspectives of diverse stakeholders in the housing sector on the opportunities and obstacles involved in including health-related criteria in LIHTC funding decisions. Our interviewees demonstrated a growing desire within the housing sector to address health needs but, with the exception of green building criteria, a lack of clear standards on best practices. Stakeholders noted the challenges of effectively partnering with local health institutions, the need to develop sustainable payment mechanisms for health-related services, and the importance of locating developments near health-promoting resources. By describing mechanisms for integrating health services into the affordable housing infrastructure, this study helps lay the groundwork for the development of cross-sector partnerships.